An Investigation of Global and Regional Integration of ASEAN Economic Community Stock Market: Dynamic Risk Decomposition Approach. Issue 9 (1st September 2016) - Lee, Geesun; Jeong, Jinho
ABSTRACT: This article investigates the dynamic pattern of stock market relations between the ASEAN Economic Community (AEC) and two major stock markets: China and the United States. A GARCH risk decomposition model is developed to reflect the time-varying market integration. The primary findings of this study are as follows. First, the AEC is more integrated with the regional stock market than with the global stock market. Second, the movement in the AEC stock market is mainly driven by domestic economic situations. Third, external shocks only affect the level of integration of the AEC temporarily. Finally, international investors are able to significantly reduce unsystematic risk by adding an AEC market portfolio into their existing portfolios.